(untitled) (CIPEEX, 2025)
INTRODUCTION: Cancer is considered a public health problem worldwide, with estimates of global growth. Among cancer patients, approximately 5% to 10% develop wounds, either due to the tumor or metastasis, known as malignant neoplastic lesions (MNLs). These wounds occur due to an oncological lesion associated with genetic mutations that affect the control of cell proliferation, resulting in an infiltration of malignant tumor cells into the skin structures, resulting in the formation of a wound that ends up destroying the entirety of the epithelium, causing disordered cell proliferation. OBJECTIVE: Investigate oncological lesions and assess the knowledge of heath professional METHODS: This is an integrative literature review using Scielo and PubMed searches, using the descriptors "Oncological Lesions", "Wounds", "Neoplasia" and "Malignancy". Was only used articles in Portuguese, applying the Boolean operator AND. The inclusion criteria were articles published in the last 5 years, publications that did not meet these criteria or were unrelated to the central objective were excluded. RESULTS: According to the articles reviewed, the study involved 11 experts, predominantly PhDs, who validated an 18-question questionnaire on malignant neoplastic wounds (MNW), covering definition, incidence, oncogenesis, staging, treatment, and nursing interventions. The validation showed a good degree of inter-rater agreement (Kendall’s coefficient = 0.0941). It was identified that only 63% of Brazilian states have State Oncology Care Plans, most of which are not in compliance with Ordinance No. 874. Three categories emerged from the qualitative analysis: nursing care that transcends MNW management; team performance in assessment and care; and professionals’ feelings regarding the palliative care context. CONCLUSION: Neoplastic wounds require greater attention during treatment, as healthcare professionals deal with both the patient’s emotional and physical well-being. Furthermore, the lack of state planning for cancer treatment is notable. Further studies on the subject are needed to assist professionals and guide the development of continuing education programs.